MONITORING AREAL EXTENT AND SPATIAL DISTRIBUTION OF MANGROVES IN LEMBAR BAY AND INDUK BEACH USING LANDSAT IMAGERY - Febrian Kusuma Atmanegara; Muhammad Soimin; Didik Santoso (Fakultas Perikanan Universitas 45 Mataram, 2020)
Mangroves, a vital coastal ecosystem on earth, are threatened due to human destructive activities. Current, accurate, and reliable information on the extent of mangroves and its distribution is limited. Partial monitoring requires more comprehensive approach, especially in calculating the areal extent in a certain period of times. Therefore, monitoring by analyzing Landsat imagery could provide accurate and reliable data in determining the areal extent and spatial distribution of mangroves. We used publicly available Landsat data during the period of 1997-2018. The data, subsequently, was analyzed by supervised maximum likelihood technique and followed by a direct field validation with the total sample of 45 points (33 mangroves and 12 non-mangroves). The results of Landsat imagery analysis of 5 TM (1997) and 8 OLI (2018) reveal that approximately 82.22% and 86.67 of overall accuracy with the areal extent of mangroves in 1997 was about 44.75 Ha, increasing to about 88.83 Ha in 2018. This represents a significant increase of mangroves extent during that period as it is a result of reforestation. Rhizophora stylosa dominates the mangroves closed by Cemara beach, while Sonneratia caseolaris is abundant in the estuary. This information could be used as a basis for policy makers to create a sound regulation to mitigate the mangroves destruction as well as forcing the conservation efforts in Lembar Bay.